Excavations at Chester. Roman Land Division and a Probable Villa in the Hinterland of Deva Excavation at Saighton Army Camp, Huntington, Chester - Wood, Philip N. (2023)
Excavations at Chester. Roman land division and a probable villa in the hinterland of Deva reports on excavations carried out by Northern Archaeological Associates (NAA) at Saighton Camp - a former British Army training camp - located to the south of the Roman legionary fortress of Chester (Deva Victrix) which revealed important and extensive Roman period remains. Part of a high-status settlement of second- to fourth-century date, together with a regular field system laid out over more than 20 hectares, were encountered.The excavated settlement appears to be an ancillary area to a much larger site, the centre of which lies to the south and is believed to be a villa. This is the closest such site to Chester, and villas are notably rare in the region. The field system was probably laid out by the legion at Deva as part of the prata legionis, agricultural lands they controlled around the fortress.